Ethical considerations for vaccination programmes in acute humanitarian emergencies - Keymanthri Moodley; Kate Hardie; Michael J Selgelid; Ronald J Waldman; Peter Strebel; Helen Rees; David N Durrheim (The World Health Organization, 2013)
Humanitarian emergencies result in a breakdown of critical health-care services and often make vulnerable communities dependent on external agencies for care. In resource-constrained settings, this may occur against a backdrop of extreme poverty, malnutrition, insecurity, low literacy and poor infrastructure. Under these circumstances, providing food, water and shelter and limiting communicable disease outbreaks become primary concerns. Where effective and safe vaccines are available to mitigate the risk of disease outbreaks, their potential deployment is a key consideration in meeting emergency health needs. Ethical considerations are crucial when deciding on vaccine deployment. Allocation of vaccines in short supply, target groups, delivery strategies, surveillance and research during acute humanitarian emergencies all involve ethical considerations that often arise from the tension between individual and common good. The authors lay out the ethical issues that policy-makers need to bear in mind when considering the deployment of mass vaccination during humanitarian emergencies, including beneficence (duty of care and the rule of rescue), non-maleficence, autonomy and consent, and distributive and procedural justice.